2000
DOI: 10.1093/rheumatology/39.5.490
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with functional impairment in symptomatic knee osteoarthritis

Abstract: Function in symptomatic knee OA is determined more by pain and obesity than by structural change, at least as seen on plain X-ray. Our study provides further support for interventions targeting anxiety and helplessness in knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
287
6
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(333 citation statements)
references
References 36 publications
26
287
6
14
Order By: Relevance
“…This action minimizes the forces transmitted to the proximal joints in initial contact in gait. Accordingly, this muscle is important in knee stabilization and its weakness can generate abnormal stress mechanisms in the joint, leading to pain, 13 and resulting in postural instability and often falls. 2 In a study by O'Reilly et al 8 the authors also demonstrated inverse correlation of muscle strength of the quadriceps muscle in individuals with knee OA and reports of pain and functional disability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This action minimizes the forces transmitted to the proximal joints in initial contact in gait. Accordingly, this muscle is important in knee stabilization and its weakness can generate abnormal stress mechanisms in the joint, leading to pain, 13 and resulting in postural instability and often falls. 2 In a study by O'Reilly et al 8 the authors also demonstrated inverse correlation of muscle strength of the quadriceps muscle in individuals with knee OA and reports of pain and functional disability.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant aspect is the association of the presence of pain with the occurrence of stiffness and alterations in functional activities, especially those related to knee flexion. 5,13,17 Leveille et al 17 demonstrated that in elderly individuals with OA the greatest difficulty in the performance of daily functions was related to muscle weakness developed in avoiding the execution of tasks that produced pain, such as climbing stairs or walking for a longer distance. Therefore, pain is an important and common clinical symptom in patients with OA, and can constitute a limiting factor of functional ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results have demonstrated that psychological factors (9 -13), demographic and clinical factors (9,11,14), biomechanical factors (10,15,16), and treatment modalities (10,17) are associated with disability. It is not known, however, whether these factors also predict future disabil-ity.…”
Section: Introductionmentioning
confidence: 99%